An Overview of Proteases: Production, Downstream Processes and Industrial Applications. Issue 3 (3rd July 2021) - Gimenes, Nathiele Contrera; Silveira, Edgar; Tambourgi, Elias Basile
Abstract : Peptidases or proteases are enzymes with the ability to break peptide bonds. They have been investigated due to their industrial applications in products such as foods and detergents. This review provides an update of protease characteristics, production, downstream processes and industrial applications. Proteases are predominantly produced by microorganisms using submerged and solid-state fermentations. The bottleneck of production is found in downstream processes, which can account for 70 to 90% of the total production cost. Precipitation is used in addition to extraction using aqueous two-phase systems (ATPSs). ATPS extraction has emerged as a recovery method enabling to clarify, to concentrate, and to purify the target biomolecule in a single operation. However, efficient cost-effective strategies need to be improved in order to provide peptidases to industries on a sufficient level. The search for new protease sources has been encouraged in order to meet industrial application requirements.